Pengaruh Good Corporate Governance, Pengendalian Internal Dan Kesesuaian Kompensasi Terhadap Pencegahan Kecurangan (Fraud) Dalam Pengelolaan Dana Bumdes: Kata kunci: good corporate governance, pengendalian internal, kesesuaian kompensasi, pencegahan kecurangan. - Luh Tusna Putri Darmayanti; Nyoman Ari Surya Darmawan (Vokasi : Jurnal Riset Akuntansi, 2024)
The implementation of this research involves finding out the influence of good corporate governance, internal control and appropriate compensation on preventing fraud in managing the flow of BUMDes funds. This research is quantitative research with primary data sources in the form of questionnaires with 65 respondents. The method used in the research sample selection process is purposive sampling technique. The data analysis techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination tests and t tests with the help of STATA. The research results show that good corporate governance, internal control and compensation suitability have a substantially positive influence on fraud prevention in the management of BUMDes funds in Sawan District.